People's Republic of China-Hong Kong Special Administrative Region : Financial Sector Assessment Program-Technical Note-Insurance Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2021)
This note provides an update and assessment of developments in insurance supervision since 2014. It is part of the 2020 Financial Sector Assessment Program (FSAP) for the Hong Kong SAR (HKSAR) and draws on discussions there from September 10 to 24, 2019. It has not been updated for the impact of recent global events associated with the COVID-19 pandemic. The insurance sector is large, especially long-term (life) insurance, highly international and has been growing steadily. The long-term market is amongst the world's largest, particularly by penetration (premiums to GDP). Growth has been supported by the popularity of savings products, including sales of policies to Mainland Chinese visitors (MCVs), although these have declined from their peak. The general insurance sector, though comprising many more companies, is relatively small and spread over many lines. The authorities have identified scope for growth in protection policies as well as opportunities for captive and specialty lines related to China's Belt and Road Initiative. Tax incentives have supported the recent successful introduction of new annuity and health insurance products. Although foreign-owned companies account for a large share of business, the HKSAR is the home of three major domestic groups operating internationally.